'Dual' labour market? Patterns of segmentation in European labour markets and the varieties of precariousness. (November 2021) - Seo, Hyojin
This article aims to empirically explore how European labour markets are segmented and who the outsiders are. The article moves beyond the dichotomous approach to understanding labour market division, often based solely on examining employment relationships. Taking a multi-dimensional approach to defining labour market precariousness, this study incorporates aspects such as income, job prospects and subjective insecurity. Latent Class Analysis is used on data taken from the 2015 European Working Conditions Survey to extend the traditional definition of outsider-ness. Four labour market segments are found: insiders and three different types of outsiders : typical outsiders, dead-end insiders and subjective outsiders . Looking at the cross-national aspect, variations are found in the segmentation patterns, especially in terms of who the outsiders are. The findings show the need to examine various aspects of labour precariousness in order to capture the complexity of post-industrialised labour markets and identify different types of outsiders across Europe that need to be protected for building a more cohesive society.